Dialect derivatives with the suffix -ica from the semantic field ‘man’ - Horvat, Mojca (Jezikoslovni zapiski, 2015)
This article shows a possible secondary interpretation of the dialect material in volume 1 of Slovenski lingvistični atlas (Slovenian Linguistic Atlas, SLA 1), published in 2011. It focuses on derivatives with the suffix -ica that were classified according to the morpheme structure of the suffix and the part-of-speech category of the motivated word. The frequency and geographical distribution of the expressions analyzed are determined using a word-formation map.